A low-deflection anti-skid composite material electric pole and preparation method thereof

By adopting an optimized winding angle and layout in fiber composite poles, combined with the use of aromatic polyurethane and nylon fiber bundles, the problems of poor anti-slip properties and large deflection of the poles are solved, and higher performance optimization is achieved.

CN116163577BActive Publication Date: 2025-04-15SHANTOU POWER SUPPLY BUREAU OF GUANGDONG POWER GRID CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211492851.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-04-15
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

The existing fiber composite poles have poor anti-slip properties and large deflection, and it is difficult to effectively utilize the excellent properties of high-strength fibers.

Method used

Using a composite material of multi-layer high-strength fiber and aromatic polyurethane prepreg, the winding angle determined by the algorithm and the winding method of high-strength fibers is added to improve anti-slip performance by combining the fiber layout of the annular and longitudinal winding.

Benefits of technology

It significantly reduces the bending deflection of the pole, improves the anti-slip performance and UV resistance, and enhances the overall performance of the pole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116163577B_ABST
    Figure CN116163577B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-deflection anti-skid composite material pole, which is a composite material of multiple layers of high-strength fibers and polyurethane prepregs, with the innermost two layers of high-strength fibers and the middle layer being wound at a winding angle obtained by an optimization algorithm and different high-strength fibers to meet the stiffness requirements. The circumferential winding is an angle between the winding angle and the pole cross section of 5° to 25°, and the longitudinal winding is an angle between the winding angle and the pole cross section of 60° to 85°. The low-deflection anti-skid composite material pole of the present invention achieves the purpose of structural optimization according to the stiffness requirements during the optimization of the rigidity of the composite material, and lays the high-strength fibers at the optimal winding angle, thereby solving the problems of large deflection and low stiffness of the existing poles; the outermost layer is an anti-skid and wear-resistant nylon fiber bundle pre-impregnated with aliphatic polyurethane wound in the circumferential direction, thereby improving the anti-ultraviolet and anti-skid properties of the pole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fiber composite material, in particular to a low-flexure anti-skid composite material electric pole and a preparation method thereof. Background Art

[0002] Traditional poles are mostly made of wood, steel and concrete. Many of these poles have the problems of large size, heavy weight, difficult to carry, easy to corrode, short life, difficult construction, transportation and operation and maintenance. Composite materials have been more and more widely used in the field of power transmission and distribution in recent years due to their high strength, light weight, corrosion resistance, good electrical insulation, long service life, convenient transportation and construction.

[0003] Compared with traditional poles, glass fiber reinforced composite pole towers have the advantages of high specific strength, high specific modulus, good toughness, good insulation performance, excellent corrosion resistance, low maintenance difficulty and frequency, and good designability. At the same time, composite poles are light in weight, not easy to break under force, and strong in wind resistance. They play an increasingly important role in post-disaster circuit repair and bypass power supply. With the widespread application of composite poles, the requirements for the load-bearing capacity, surface anti-slip performance, durability and bending resistance of composite poles are constantly increasing. How to more effectively utilize the excellent properties of high-strength fibers and improve design potential has become the goal pursued by composite pole structure design. Summary of the invention

[0004] Aiming at the problem that the existing fiber-wound fiber composite material poles have poor anti-skid performance and large deflection due to the high difficulty of continuous laying and fixing, the present invention provides a low-deflection anti-skid composite material pole, which is a composite material of multiple layers of high-strength fibers and aromatic polyurethane prepreg. The innermost two layers of high-strength fibers are wound in a hoop, and the middle layer is wound using the winding angle obtained by the optimization algorithm and different high-strength fibers to meet the stiffness requirements. The hoop winding angle is 5° to 25° with the pole cross section, and the longitudinal winding angle is 60° to 85° with the pole cross section.

[0005] The high-strength fiber of the present invention adopts chemical fiber with high strength, such as glass fiber, basalt fiber or carbon fiber, which is impregnated with aromatic polyurethane prepreg and then wound on the surface of the rod-shaped mold, and serves as the reinforcing fiber composite material layer of the rod-shaped mold after solidification. The specification of the high-strength fiber of the present invention is 2000-3000tex, and the tensile strength at break is not less than 0.45N / tex.

[0006] Furthermore, two layers of nylon fiber bundles with a diameter of 0.5-1.5 mm are symmetrically wound clockwise and counterclockwise on the surface of the low-flexure anti-skid composite material pole of the present invention, and the surface of the nylon fiber bundles is impregnated with aliphatic polyurethane prepreg, and the winding angle is 5° to 25° with the cross section of the pole, and the spacing between the nylon fiber bundles is not less than 300 mm.Figure 1 shown.

[0007] The aromatic polyurethane prepreg of the present invention is composed of the following components in parts by weight: 120-190 parts of CR4555 / 202C-B isocyanate, 100-120 parts of CR4555 / 100C-B isocyanate, 80-120 parts of CR4555 / 101C-A polyol, and 90-110 parts of CR4555 / 203C-A polyol. The aliphatic polyurethane has anti-ultraviolet performance, and the nylon fiber bundle is arranged on the outermost side to give the pole anti-ultraviolet performance. The weight ratio of polyol to isocyanate in the aliphatic polyurethane prepreg of the present invention is 100:108.

[0008] The method for preparing the low-deflection anti-skid composite material electric pole of the present invention comprises the following steps:

[0009] 1) Bending simulation

[0010] The inner surface of the designed composite pole is modeled using Creo and imported into the ACP pre-processing module under the Workbench platform. The inner surface of the pole is divided into 10mm surface meshes. The ACP pre-processing module is used to select the ply material, ply angle, and ply thickness of the corresponding composite pole, and the composite pole is plyed. The pole model and the supporting base are imported into the statics analysis module, and bending moment is applied to the combined model. The deflection simulation analysis is performed using the nonlinear statics solver.

[0011] 2) Laying angle optimization

[0012] The generated pole model is parameterized using the ACP module. In the post-processing results of the deflection analysis, the bending deflection of the pole and the PUCK criterion IRF factor are selected as output parameters. The input and output parameters are imported into the parameter manager. The range of input and output parameters is selected and the test set is set according to the central composite design experimental method. The kriging response surface construction method is selected using the generated test set to construct a second-order response surface, in which the ply angle and ply material are the input parameters of the response surface, and the composite pole deflection and IRF factor are the output parameters of the response surface. Based on the generated response surface, the MOGA optimization algorithm is used to optimize the ply material and ply angle of the composite pole, and the optimal ply material combination and ply angle are obtained.

[0013] 3) Preparation

[0014] Weigh the aromatic polyurethane prepreg by weight, mix and stir evenly, and transfer to a long strip container; weigh the aliphatic polyurethane prepreg by weight, mix and stir evenly, and transfer to a long strip container;

[0015] 4) Impregnation

[0016] The high-strength fiber and nylon fiber bundle used for the electric pole are respectively immersed in the aromatic polyurethane prepreg and aliphatic polyurethane prepreg prepared in step 1);

[0017] 5) Entanglement

[0018] The high-strength fiber impregnated with aromatic polyurethane prepreg is wound from the root to the top of the rod-shaped mold according to the winding setting, with a total winding thickness of 10-15 mm, and then the nylon fiber bundle impregnated with aliphatic polyurethane prepreg is wound from the bottom to the top of the rod-shaped mold according to the winding setting;

[0019] 5) Curing

[0020] The stripped pole wound in step 4) is cured at 80° C.-95° C. for 2-5 hours, and a low-deflection anti-skid composite pole is obtained after demoulding.

[0021] The low-deflection, anti-skid composite material electric pole of the present invention achieves the purpose of structural optimization according to the conditions required during the optimization of the rigidity of the composite material, lays the fibers at the optimal winding angle, solves the problems of large deflection and low rigidity of the existing electric poles, and utilizes the anti-skid and wear-resistant nylon fiber bundle of the outermost layer of annularly wound aliphatic prepreg to improve the anti-ultraviolet and anti-skid properties of the electric pole.

[0022] Specifically, the present invention adopts simulation optimization means to determine the optimal ply material combination and ply angle in the early stage, which also involves the following specific details: 1. The ACP pre-processing module also includes the setting of composite pole materials under the Workbench platform. The inner surface of the pole adopts the surface meshing form, and the mesh length is 10 mm. After the inner surface of the pole is imported into the ACP pre-processing module, it is necessary to associate the coordinate system, select the composite material properties, ply growth direction, single-layer ply angle and gradient ply thickness. 2. Using the static analysis module, it is necessary to set the material, base mesh, set the contact form between the pole and the base, set the solver and post-processing results for the assembled pole model, and batch solve the pole deflection and IRF factor under different working conditions in the form of multiple load steps. 3. Setting the test set includes the selection of multiple test methods, specifically Central Composite Design or Optimal Space-Filling Design or Box-Behnken Design or Sparse Grid Initialization or Latin Hypercube Sampling Design test design methods. 4. The choice of response surface construction method, specifically Genetic Aggregation or Standard Response Surface or Kriging or Non-Parametric Regression or NeuralNetwork or Parse Grid response surface construction method. 5. The optimization algorithm, specifically Screening or MOGA or NLPQL or MISQP and other optimization algorithms.

[0023] The present invention optimizes the ply angle of the test composite pole through a simulation optimization method, guides the winding of the composite pole through an optimization model, and optimizes multiple parameters while meeting the bending deflection, which can effectively reduce the test workload and improve the accuracy of the design analysis. Combined with the manufacturing process introduced in the invention, the bending deflection of the pole can be greatly reduced. The anti-skid and wear-resistant nylon fiber bundle with the outermost layer of aliphatic prepreg wound in an annular direction can also improve the anti-ultraviolet and anti-skid properties of the pole. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of the outer layer of aliphatic impregnated nylon anti-slip yarn bundle winding of the present invention;

[0025] Figure 2 This is a schematic diagram of the ply angle of Example 1;

[0026] Figure 3 This is a schematic diagram of the response surface for optimizing the winding angle of the composite material in Example 2;

[0027] Figure 4This is a schematic diagram of the ply angle after optimization in Example 1;

[0028] Figure 5 This is a SEM image of a single-layer fiber cross section of the fiber composite material of Example 1;

[0029] Figure 6 This is a SEM image of a cross section of a multilayer fiber of the fiber composite material of Example 2;

[0030] Figure 7 This is a SEM image of a single-layer fiber cross section of the fiber composite material of Example 1;

[0031] Figure 8 This is a SEM image of the cross section of the multilayer fiber composite material of Example 2. DETAILED DESCRIPTION

[0032] The present invention is described below in conjunction with examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.

[0033] Example 1 The simulation method is as follows:

[0034] Step 1: Composite material layup model establishment

[0035] A composite material layup model is established by coupling Creo with ACP, the inner surface of the composite material pole is established by Creo, and the ACP module is used to design the layup of the imported inner surface of the pole, and the layup is carried out according to the actual pole winding. In this embodiment, 13 layers of layup are selected, and the outermost two layers are nylon fiber tows impregnated with aliphatic polyurethane (the angle between the layup and the cross section is 10°); the other 11 layers of layup materials are glass fibers impregnated with aromatic polyurethane, of which the innermost two layers have an angle of 10° with the cross section, and the remaining layers are cross-laid at 10° and 80°. The layup schematic diagram is shown in the figure. Figure 2 shown.

[0036] Step 2: Bending performance simulation

[0037] The model after ACP plying is imported into the static analysis module. It should be noted that the model mesh used for data transmission here is shell unit. The bottom surface of the pole is fixed, and a bending moment of 78KN·m is applied to the side of the composite pole. Since the deflection of the composite pole is large, the solver needs to turn on the large deformation switch, set the initial increment step to 0.01 for iterative solution, and set the output parameters of the solved model. The output results include the deflection displacement of the top of the pole, the IRF factor determined by the PUCK criterion, and the single-layer Mises stress. The simulated deflection results are compared with the bending test results to verify the accuracy of the simulation model.

[0038] Example 1 The preparation method of the low-deflection anti-skid composite material pole is as follows:

[0039] 1) Preparation

[0040] According to the weight of the aromatic polyurethane prepreg, 120 parts of CR4555 / 202C-B isocyanate, 120 parts of CR4555 / 100C-B isocyanate, 80 parts of CR4555 / 101C-A polyol, and 110 parts of CR4555 / 203C-A polyol were weighed, mixed and stirred evenly, and transferred to a long container; according to the weight of the aliphatic polyurethane prepreg, 100 parts of CR4555 / 101C-A polyol and 108 parts of CR4555 / 100C-B isocyanate were weighed, mixed and stirred evenly, and transferred to a long container;

[0041] 2) Impregnation

[0042] Taking a glass fiber with a specification of 2000 tex and a tensile strength of 0.45 N / tex and immersing it into the aromatic polyurethane prepreg prepared in step 1), taking a PA6 nylon fiber bundle with a diameter of 0.5 mm and immersing it into the aliphatic polyurethane prepreg prepared in step 1);

[0043] 3) Entanglement

[0044] The high-strength fiber impregnated with aromatic polyurethane prepreg in step 2) is wound according to the technical indicators in Table 1, with a total thickness of 0.8 mm, the innermost two layers are wound from the root to the top of the rod-shaped mold, and the third layer is wound from the part above the bottom to the top, and the cycle is repeated to finally obtain a pole ply thickness of 10 mm, and finally the nylon fiber bundle impregnated with aliphatic polyurethane prepreg is wound symmetrically clockwise and counterclockwise from the bottom to the top of the rod-shaped mold in two layers, the winding angle is 10° with the cross section of the pole, and the winding spacing is 300 mm;

[0045] 4) Curing

[0046] The product after winding in step 3) is cured at 80° C. for 4 hours, and a low-deflection anti-skid composite material pole is obtained after demoulding.

[0047] The low-deflection anti-skid pole obtained in Example 1 is 12 meters long, and the mechanical properties comparison is shown in Table 3. The implementation standard is GBT41491-2022 "Composite poles and towers for distribution networks".

[0048] Table 1. Comparison of simulated and actual deflections in Example 1

[0049]

[0050] Example 2 The simulation method is as follows:

[0051] Step 1: Establish a parameterized model of the bending deflection of composite poles

[0052] The composite pole is laid in the same manner as step 1 in Example 1, and the output of each layer angle is transmitted to the parameter set as an input parameter. The layer angle parameters are determined from the inner layer to the outer layer as P1-P11, which will not be described in detail here. The model after the ACP layer is completed is imported into the static analysis module in the same manner as step 2 in Example 1, and the initial incremental step is set to 0.01 for static solution. The output parameters of the solved model are set to determine that the top deflection of the pole is P12, and the IRF factor of the comprehensive composite layer is P13.

[0053] Step 2: Experimental group generation

[0054] The design exploration module of the Workbench platform was used for experimental design. Since the ply angle of the composite pole is a continuous variable, the Central Composite Design design method was used to select the parameter variation range of the input parameters and obtain 149 groups of experimental parameters.

[0055] Step 3: Construct a response surface model

[0056] According to the experimental parameter set constructed in step 2, the Kriging response surface construction method is selected to complete the construction of the response surface model. Kriging is a multidimensional interpolation technology suitable for highly nonlinear complex engineering optimization problems. The function expression is as follows (1):

[0057]

[0058] Where R is the correlation matrix, rT(x) is the vector of the relationship between unknown points and known points, and the resulting response surface is as follows: Figure 3 ;

[0059] Step 4: MOGA Optimization Model

[0060] Using the response surface model constructed in step 3 and the experimental group in step 2, the MOGA optimization algorithm was selected to optimize the ply angle. Finally, three groups of optimized ply angle combinations of composite poles were obtained, as shown in Table 2. The optimization objective expression of the multi-objective optimization in this step is shown in formula (2). For the convenience of description, it is named P α For the hoop ply, P β The objective function of the construction requires that the top deflection of the pole is less than 1000mm, and the ply IRF factor calculated by the PUCK criterion is less than 1. The optimized ply is as follows Figure 4 shown.

[0061]

[0062] Table 2

[0063]

[0064] Example 2 The preparation method of the low-deflection anti-skid composite material pole is as follows:

[0065] 1) Preparation

[0066] Weigh 140 parts of CR4555 / 202C-B isocyanate, 100 parts of CR4555 / 100C-B isocyanate, 90 parts of CR4555 / 101C-A polyol, and 105 parts of CR4555 / 203C-A polyol based on the weight of the aromatic polyurethane prepreg, mix and stir evenly, and transfer to a long strip container; weigh 100 parts by weight of CR4555 / 101C-A polyol and 108 parts by weight of CR4555 / 100C-B isocyanate, mix and stir evenly, and transfer to a long strip container;

[0067] 2) Impregnation

[0068] Taking glass fiber with a specification of 2500 tex and a tensile strength of 0.5 N / tex and immersing it into the aromatic polyurethane prepreg prepared in step 1), taking a nylon fiber bundle with a diameter of 1 mm and immersing it into the aliphatic polyurethane prepreg prepared in step 1);

[0069] 3) Entanglement

[0070] The high-strength fiber impregnated with aromatic polyurethane prepreg in step 2) is wound according to the technical indicators in Table 1, and the inner two layers are wound from the root to the top of the rod-shaped mold. Under the premise of uniform winding of the winding machine, the thickness of the single-layer high-strength fiber ply is not less than 0.8 mm, and the total winding thickness of the high-strength fiber is 11 mm. Finally, the nylon fiber bundle impregnated with aliphatic polyurethane prepreg is wound symmetrically clockwise and counterclockwise from the bottom to the top of the rod-shaped mold in two layers, with a winding angle of 15° with the axis of the pole and a winding spacing of 120 mm.

[0071] 4) Curing

[0072] The rod-shaped mold after winding in step 3) is cured at 90° C. for 3 hours, and a low-deflection anti-skid composite material electric pole is obtained after demoulding.

[0073] The low-deflection anti-skid pole obtained in Example 2 is 12 meters long, and the mechanical properties comparison is shown in Table 3. The implementation standard is GBT41491-2022 "Composite poles and towers for distribution networks".

[0074] Table 3. Comparison of simulated and actual deflections in Example 2

[0075]

[0076] Figure 1 This is a schematic diagram of the outer layer of aliphatic impregnated nylon anti-slip yarn winding of the present invention, Figure 2 This is a schematic diagram of the ply angle of Example 1. Figure 3 This is a schematic diagram of the response surface for optimizing the winding angle of the composite material in Example 2. Figure 4 This is a schematic diagram of the ply angle after optimization in Example 1. Figure 5-Figure 8 They are SEM images of single-layer fiber and multi-layer fiber cross-sections of the fiber composite materials of Examples 1-2, respectively. It can be seen from the images that the single-layer fibers of Examples 1-2 are tightly wound, the aromatic polyurethane is filled evenly without gaps, there is no obvious interlayer separation between different fiber layers, the fibers are evenly arranged, and the interlayer angles are clear.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a low-flexure anti-skid composite material pole, wherein the low-flexure anti-skid composite material pole comprises a composite material of multiple layers of high-strength fibers and polyurethane prepreg, wherein the innermost two layers of high-strength fibers are circumferentially wound, and the middle layer is wound using a winding angle obtained by an optimization algorithm and different high-strength fibers to meet stiffness requirements, wherein the circumferential winding has an angle of 5° to 25° with the cross section of the pole, and the longitudinal winding has an angle of 60° to 85° with the cross section of the pole; It is characterized in that The method for preparing the low-deflection anti-skid composite material pole comprises the following steps: 1) Simulation The inner surface of the designed composite pole was modeled using Creo and imported into the ACP pre-processing module under the Workbench platform. The inner surface of the pole was meshed with a 10 mm surface. The ACP pre-processing module was used to select the corresponding ply material, ply angle, and ply thickness of the composite pole, and the composite pole was plyed. The pole model and the supporting base were imported into the statics analysis module, and a bending moment was applied to the combined model. The nonlinear statics solver was used to perform deflection simulation analysis. 2) Optimization of ply angle The generated pole model is parameterized using the ACP module. In the post-processing results of the deflection analysis, the bending deflection of the pole and the PUCK criterion IRF factor are selected as output parameters. The input and output parameters are imported into the parameter manager. The range of input and output parameters is selected and the test set is set according to the central composite design experimental method. The kriging response surface construction method is selected using the generated test set to construct a second-order response surface, in which the ply angle and ply material are the input parameters of the response surface, and the composite pole deflection and IRF factor are the output parameters of the response surface. Based on the generated response surface, the MOGA optimization algorithm is used to optimize the ply material and ply angle of the composite pole, and the optimal ply material combination and ply angle are obtained. 3) Preparation Weigh the aromatic polyurethane prepreg by weight, mix and stir evenly, and transfer to a long strip container; weigh the aliphatic polyurethane prepreg by weight, mix and stir evenly, and transfer to a long strip container; 4) Impregnation All high-strength fibers and nylon fiber bundles used for the electric poles are immersed in the aromatic polyurethane prepreg and aliphatic polyurethane prepreg prepared in step 3) respectively; 5) Entanglement The high-strength fiber impregnated with aromatic polyurethane prepreg is wound from the root to the top of the rod-shaped mold according to the winding setting, with a total winding thickness of 10-15 mm, and then the nylon fiber bundle impregnated with aliphatic polyurethane prepreg is wound from the bottom to the top of the rod-shaped mold according to the winding setting; 6) Curing The rod-shaped mold after winding in step 5) is cured at 80° C.-95° C. for 2-5 hours, and after demoulding, a low-deflection anti-skid composite material electric pole is obtained.

2. The method for preparing a low-deflection anti-skid composite material pole according to claim 1, characterized in that: Two layers of nylon fiber bundles with a diameter of 0.5-1.5 mm are symmetrically wound clockwise and counterclockwise on the surface of the low-flexure anti-skid composite material pole, the surface of the nylon fiber bundles is impregnated with aliphatic polyurethane prepreg, the winding angle is 5°~25° with the pole cross section, and the spacing between the nylon fiber bundles is not less than 300 mm.

3. The method for preparing a low-deflection anti-skid composite material pole according to claim 1, characterized in that: Each layer of high-strength fiber is selected from one of glass fiber, basalt fiber or carbon fiber.

Citation Information

Patent Citations

  • Composite material transmission tower

    CN102127986A

  • Tensile and antiskid composite electric pole

    CN215803606U